Recurrence Relation for The Moments of Order Statistics from The Beta Exponential-Geometric Distribution - Jaleel Najm, Ali; Jabbari Khamnei, Hossein; Makouei, Somayeh (Statistics, Optimization & Information Computing, 2025)
In this paper, a novel cumulative distribution function (cdf) for beta exponential-geometric (BEG) distribution, through two distinct practical frames, is developed. However, the presented models are obviously more pragmatic than the ones being demonstrated in previous works, in the case of extending further relations. Then, using the exhibited cdfs, certain recurrence relations for the single and product moments of the order statistics of a random sample of size n arising from BEG distribution are derived.